Nurturing Is Not Enough: A Case Study on Social Justice, Caring, and Discipline. Issue 2 (April 2019) - Smith, Darrick; Yeh, Christine J.
We explore the dynamics of nurturing, caring, and enabling in a social justice school and how a problematic context of educational enabling can develop when notions of nurturing are not balanced with consistent disciplinary consequences. In-depth interviews were conducted with eight school staff, teachers, and a student at a social justice urban school. Observational data and institutional documents were also analyzed, and three main themes emerged revealing the tension between nurturing and enabling: (a) sentimentalist standards, (b) perceptions of authority as oppressive, and (c) contradictions in social justice values. We discuss implications for school policy, multicultural education, and school leadership.